FUSING THE VOICES: THE APPROPRIATION AND INSTITUTIONALIZATION OF THE WASTE LAND - Fletcher, Martin John (Cadernos do IL, 2016)
Although T. S. Eliot’s masterpiece, The Waste Land, is a defiantly enigmatic and bewildering poem, the text still occupies a central place in the literary canon nearly a century after its conception. Eliot’s initial idea was to publish the work as several separate poems, yet despite this, The Waste Land is still studied as a unified whole with a unifying voice and an identifiable “message”. In this paper I argue that the poem’s reputation today rests upon a mass of critical discourse which insists on interpreting “meaning” at the expense of considering the poem’s musical, allusive and hypnotic power.